2003
DOI: 10.1080/1350485032000056855
|View full text |Cite
|
Sign up to set email alerts
|

Testing the initial endowment effect in experimental auctions

Abstract: In experimental auctions, participants are usually given an initial endowment or cash compensation that will cover the costs associated with their bids in the experiment as well as their participation time. This study analyses participants' bids in a randomly binding second-price auction to test the effect of the initial endowment on participants' willingness-to-pay estimates. Three different endowments: $2, $4, and $6 are used to compensate participants in an experimental auction. It is found that participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 5 publications
0
41
0
Order By: Relevance
“…This is similar to Oparinde et al (2014), who found a 24% increase in WTP due to a nonpayment effect. The present study and Oparinde et al (2014) have demonstrated that it is feasible to conduct revealed preference-elicitation experiments in African countries in an out-of-pocket payment context, while avoiding the cash-in-hand effect bias introduced by participation fees, as noted in previous studies (Loureiro et al 2003;Corrigan and Rousu 2006;Morawetz et al 2011).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 85%
“…This is similar to Oparinde et al (2014), who found a 24% increase in WTP due to a nonpayment effect. The present study and Oparinde et al (2014) have demonstrated that it is feasible to conduct revealed preference-elicitation experiments in African countries in an out-of-pocket payment context, while avoiding the cash-in-hand effect bias introduced by participation fees, as noted in previous studies (Loureiro et al 2003;Corrigan and Rousu 2006;Morawetz et al 2011).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 85%
“…The latter pretext is commonly used in Africa to detach pecuniary endowments from their 'gift' or 'payment-for-service' context. It elegantly avoids the fee being seen as a quid pro quo for which participants should reciprocate (Lusk and Shogren, 2007), and which may bias the bids (Loureiro, Umberger, and Hine, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in dispersed rural populations, BDM is sometimes preferred over other auction mechanisms, as it allows for eliciting valuations from individuals (home-use testing) and because carrying out group auctions (central-location testing) can be expensive and time-consuming. 39 Another reason is that laboratory auctions may require higher participant fees, which have shown to positively affect valuations, [40][41][42] a phenomenon known as an income endowment effect. 43 Such monetary incentives may be of particular relevance when considering students rather than adults, 44 despite the fact that both types of respondents, commonly targeted in WTP research, are not expected to bid significantly differently.…”
Section: Introductionmentioning
confidence: 99%